PERAN CERITA RAKYAT DARA MUNING DALAM PENGUKUHAN SISTEM BUDAYA - NFN Musfeptial (tuahtalino, 2019)
This study is entitled Role of Dara Muning Folklore in the Culture System Construction. This study seeks the role of West Kalimantan folklore, especially Dara Muning in the establishment of a cultural system. The theoretical framework used as the basis for this study is an understanding of the theory of literary anthropology. Anthropological theory in the field of literature is basically a theory that focuses on the relationship between literary work and the society that creates or supports the literary work. So that literary works have a cultural dimension of benefits. This research is a qualitative research in a literary perspective. Qualitative research is research that intends to understand the phenomenon of what is experienced by the subject of research such as behavior, perceptions, motivations, actions and others holistically and by way of descriptions in the form of words and language in a specific context that is experienced and by utilizing various natural methods. Thus, a qualitative approach basically provides space for researchers to describe and interpret the meaning of existing data and facts contextually. The results of the study show the role of folklore in the strengthening of existing cultural systems. Especially the West Kalimatantan Dayak culture.